2016
DOI: 10.1039/c6cy01268j
|View full text |Cite
|
Sign up to set email alerts
|

Isomerisation versus carbonylative pathways in the hydroxy-carbonylation, methoxy-carbonylation, and amino-carbonylation of N-tosyl-3-pyrroline

Abstract: Abstract:The reactivity of N-tosyl-3-pyrroline is significantly lower than that of mono-substituted alkenes in Pd catalysed methoxycarbonylation reactions. For example, most bulky diphosphine/ Pd catalysts, including the well-known Pd catalyst derived from 1,2-bis(Di-TertButylPhosphinoXylene (DTBPX), were found to give no product at all in the methoxycarbonylation of N-tosyl-3-pyrroline. The competing pathways in methoxycarbonylation of N-methane-sulfonyl-3-pyrroline using Pd/ DTBPX were studied using DFT calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 54 publications
(22 reference statements)
0
21
0
Order By: Relevance
“…Consistent with previous findings, changing from PPh 3 to P (OMe) 3 was followed by a drastic shift in the composition of the branched esters from 41% to 82% (Table , entries 1 and 9). This trend has been associated with minimal steric hindrance to give the bulkier branched esters …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous findings, changing from PPh 3 to P (OMe) 3 was followed by a drastic shift in the composition of the branched esters from 41% to 82% (Table , entries 1 and 9). This trend has been associated with minimal steric hindrance to give the bulkier branched esters …”
Section: Resultsmentioning
confidence: 99%
“…In terms of regioselectivity, we observed the formation of more branched esters (40%) at higher catalyst loadings of 1 mol% compared to 18% of the branched esters reported at 0.25 mol% (Table , entries 5 and 6). This could be attributed to enhanced isomerization reactions at higher catalyst loadings …”
Section: Resultsmentioning
confidence: 99%
“…The inhibiting effect of CO on the isomerization as well as the inhibiting effect of 1-decene on both reactions could be confirmed by the fitting results. Fuentes et al [20] observed the same negative effect of CO on the isomerization of N-toysl-pyrroline experimentally and theoretically. In the latter, DFT calculations revealed evidence for a catalyst preequilibrium with CO where the Pd-catalyst is kept in a stable resting state with CO.…”
Section: Parameter Estimation and Discussionmentioning
confidence: 99%
“…An attempt of hydroxycarbonylation of 1-tosyl-2,5dihydro-1H-pyrrole (89) in the presence of a palladium catalyst in acetone unexpectedly resulted in ketone 91 as the main product, [81] 1-tosylpyrrolidine-3-carboxylic acid 90 is formed in trace amounts (Scheme 18).…”
Section: An Alternative Way Of Obtaining 1-(pyrrolidin-2-yl)propan-2-one Derivativesmentioning
confidence: 99%